Isolation and characterization of a high-molecular-weight polysaccharide from the slime of Pseudomonas aeruginosa. - Pier, G B (1978)
A procedure is described for isolating a high-molecular-weight polysaccharide (PS) from the slime of Pseudomonas aeruginosa immunotype 1. The resultant material, obtained from the void volume of a Sephadex G-100 column, was composed of carbohydrate and water. No lipopolysaccharide (LPS), 2-keto-3-deoxyoctonoate, heptose, phosphate, or protein was detectable, and nucleic acid contamination was generally below 1%. The carbohydrate composition of the PS was glucose, rhamnose, galactose, arabinose, and mannose. PS had a molecular weight of between 100,000 and 350,000 and did not disaggregate when chromatographed in the presence of sodium deoxycholate. An antigen immunologically indistinguishable from PS could be obtained from LPS by either acetic acid hydrolysis and column chromatography or by allowing solutions of LPS to stand at room temperature for 3 days. Some of this LPS-associated polysaccharide eluted as the void volume of a G-100 column but differed from PS by its lack of galactose and arabinose. LPS also contained an immunodeterminant not shared with PS that was detected by its stability to dilute alkali treatment (0.1 N NaOH, 37 degrees C, 2 h). PS was destroyed by alkali treatment. PS appeared to represent a form of LPS polysaccharide side chain that contains galactose and arabinose and is of a high molecular weight.